2016
DOI: 10.7189/jogh.06.010701
|View full text |Cite
|
Sign up to set email alerts
|

What is kangaroo mother care? Systematic review of the literature

Abstract: BackgroundKangaroo mother care (KMC), often defined as skin–to–skin contact between a mother and her newborn, frequent or exclusive breastfeeding, and early discharge from the hospital has been effective in reducing the risk of mortality among preterm and low birth weight infants. Research studies and program implementation of KMC have used various definitions. ObjectivesTo describe the current definitions of KMC in various settings, analyze the presence or absence of KMC components in each definition, and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 18 publications
3
110
0
4
Order By: Relevance
“…We hypothesised that these criteria would identify all ELBW neonates as unstable; however, it is possible that some administered therapies were not properly recorded in medical charts. There remains a need for an evidence-based approach to consistently define stability criteria in order to improve clinical care and facilitate research in this population [12,48].…”
Section: Instability Criteriamentioning
confidence: 99%
“…We hypothesised that these criteria would identify all ELBW neonates as unstable; however, it is possible that some administered therapies were not properly recorded in medical charts. There remains a need for an evidence-based approach to consistently define stability criteria in order to improve clinical care and facilitate research in this population [12,48].…”
Section: Instability Criteriamentioning
confidence: 99%
“…One of these emerging developments is the Kangaroo Mother Care (KMC), which is intended to deliver quality care to term and preterm newborns . KMC promotes maternal bonding immediately after birth and during hospitalisation and significantly reduces the risk of neonatal mortality as compared to conventional newborn care in resource‐limited technology settings with little equipment .…”
Section: Introductionmentioning
confidence: 99%
“…SSC is the most essential component of KMC, but the other elements are contextual (Chan et al, ). SSC involves resting the stable preterm or low‐birth‐weight infant skin‐to‐skin on the mother's bare chest in a prone and upright position.…”
Section: Introductionmentioning
confidence: 99%
“…The literature lacks a clear definition of the optimal number and duration of sessions. A recent systematic review of the SSC literature reported significant variations in the length of SSC that ranged from 2 to 22 h per day (Chan et al, ).…”
Section: Introductionmentioning
confidence: 99%